Development and validation of two SCORE-based cardiovascular risk prediction models for Eastern Europe: a multicohort study - Tillmann, Taavi; Läll, Kristi; Dukes, Oliver; Veronesi, Giovanni; Pikhart, Hynek; Peasey, Anne; Kubinova, Ruzena; Kozela, Magdalena; Pajak, Andrzej; Nikitin, Yuri; Malyutina, Sofia; Metspalu, Andres; et al. (European heart journal, 2020)
AIMS: Cardiovascular disease (CVD) risk prediction models are used in Western European countries, but less so in Eastern European countries where rates of CVD can be two to four times higher. We recalibrated the SCORE prediction model for three Eastern European countries and evaluated the impact of adding seven behavioural and psychosocial risk factors to the model. METHODS AND RESULTS: We developed and validated models using data from the prospective HAPIEE cohort study with 14 598 participants from Russia, Poland, and the Czech Republic (derivation cohort, median follow-up 7.2 years, 338 fatal CVD cases) and Estonian Biobank data with 4632 participants (validation cohort, median follow-up 8.3 years, 91 fatal CVD cases). The first model (recalibrated SCORE) used the same risk factors as in the SCORE model. The second model (HAPIEE SCORE) added education, employment, marital status, depression, body mass index, physical inactivity, and antihypertensive use. Discrimination of the original SCORE model (C-statistic 0.78 in the derivation and 0.83 in the validation cohorts) was improved in recalibrated SCORE (0.82 and 0.85) and HAPIEE SCORE (0.84 and 0.87) models. After dichotomizing risk at the clinically meaningful threshold of 5%, and when comparing the final HAPIEE SCORE model against the original SCORE model, the net reclassification improvement was 0.07 [95% confidence interval (CI) 0.02-0.11] in the derivation cohort and 0.14 (95% CI 0.04-0.25) in the validation cohort. CONCLUSION: Our recalibrated SCORE may be more appropriate than the conventional SCORE for some Eastern European populations. The addition of seven quick, non-invasive, and cheap predictors further improved prediction accuracy.
Keywords: Rusko; Czech Republic; Risk Factors; kohortové studie; Russia; Heart Disease Risk Factors; Risk Assessment; rizikové faktory; lidé; rizikové faktory kardiovaskulárních chorob; Prospective Studies; Polsko; kardiovaskulární nemoci; Humans; Cohort Studies; Poland; Česká republika; Cardiovascular Diseases; prospektivní studie; hodnocení rizik